ICT COURSES FOR PEDAGOGICAL WORKERS - ESF PROJECT - MAREŠOVÁ, Hana (Trends in education, 2010)
The article is focused on analyzing the current situation regarding the development of competences for working with ICT by pedagogical workers, in the frame of Additional Education of Pedagogical Employees (AEPE). After the termination of the government conception (State Information Policy in Education) in the Czech Republic systematic education is missing. Faculty of Education at Palacky University try to solve this situation by a systematic offer of AEPE courses aimed on using ICT across the curriculum. The ESF project focused on such training of pedagogical workers has been realized since 2010 at Faculty of Education.
Keywords: information and communication technology; Additional Education of Pedagogical Employees; key competences.